On a Road to Nowhere: Implied Declarations of Inconsistency and the New Zealand Bill of Rights Act - Geringer, Claudia (Victoria University of Wellington Law Review, 2009)
This article explores recent case law touching on the suggestion that the New Zealand courts have an implied power to formally declare that legislation is inconsistent with the rights and freedoms contained in the New Zealand Bill of Rights Act 1990. The article concludes from this case law that the prospects for the development of a formal declaratory jurisdiction of this kind in New Zealand are, if anything, receding. Further, although the Supreme Court's decision in R v Hansen [2007] 3 NZLR 1 affirms the power of the New Zealand courts to informally "indicate" the existence of such legislative inconsistencies, early indications suggest that it is unlikely that this power will be exercised on a routine basis. In the absence of legislative reform, any "dialogue" over human rights between the New Zealand courts and the political branches of government is likely to continue to be far more sporadic and sotto voce than in those countries that have legislated for an express declaration of inconsistency power.